Translating Recent Cases of Justice System Reforms into Theoretical Pillars: The Portuguese Case Study - Correia, Pedro Miguel Alves Ribeiro; Pereira, Sandra Patrícia Marques (Sociologia: Revista da Faculdade de Letras da Universidade do Porto, 2021)
The theoretical models of public administration do not always accurately represent the reality that shapes the basis of public decisions. The approaches, techniques and instruments chosen often have opposite effects. Public management reforms have become their own policy, which encompasses a group of reform menus based on several theoretical approaches (Pollitt, 2018). The objective of this work is to create a bridge between theoretical foundations and cases of recent reforms in Portuguese justice. For this, we opt for a qualitative methodological approach, using documentary analysis and content analysis as the data analysis technique. Three sets of reforms in the judicial area are presented, summarizing their objectives and their respective frameworks and results. Through the content analysis, it was possible to successfully relate the New Public Management and Governance to the reforms studied in the justice sector.